Greening the globe: Uncovering the impact of environmental policy, renewable energy, and innovation on ecological footprint - Appiah, Michale; Li, Mingxing; Naeem, Muhammad Abubakr; Sitara, Karim * (Elsevier, 2023)
This study examines the effectiveness of environmental policy in reducing ecological footprint while considering the roles of renewable energy and innovation. We employ a cross-sectional autoregressive distributed lags to analyze panel data of 29 OECD countries from 1990 to 2020. Our results indicate that environmental policy significantly reduces ecological footprint among OECD countries, with its efficacy contingent upon bio-capacity surplus/deficit and the level of industrialization. We also find that renewable energy has a favourable impact on ecological footprint reduction, while innovation improves the environmental quality of OECD countries. However, population density and industrialization were found to decrease and increase ecological footprint, respectively. The study reveals bi-directional causation between ecological footprint and all variables except for economic growth. Our findings are robust under the conditions of short-run heterogeneity, long-run homogeneity, and cross-sectional dependence.